Peran Radio Bharata Bhaktinusa Tangerang sebagai Media Literasi dalam Menyuarakan Isu dan Informasi: Studi Kasus Program Bincang Indonesia Tiongkok - Faujiah, Eva; Wati, Lina; Gusti Rahayu, Riza (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to describe the role of Radio Bharata Bhaktinusa Tangerang as a literacy media in voicingissues and information to the public. This study uses qualitative research methods using uses andgratifications theory to understand how audiences use radio as a source of information and entertainment,as well as how Radio Bharata Bhaktinusa Tangerang operates as an information medium. Data wascollected through in-depth interviews with radio listeners, observations, and conducting interviews withRadio Bharata Bhaktinusa Tangerang. The research results show that Radio Bharata Bhaktinusa plays animportant role in providing relevant and educational information, as well as helping to increase publicliteracy about social, cultural and political issues. Listening to the radio utilizes this media not only to getinformation, but also for entertainment. This research provides insight into the importance of radio aseffective communication in disseminating information and building literacy in society in order to overcomehoax news.